2006
DOI: 10.1093/rheumatology/kel437
|View full text |Cite
|
Sign up to set email alerts
|

NKT cells: manipulable managers of joint inflammation

Abstract: The importance of T cell participation in the aetiology and pathogenesis of rheumatoid arthritis (RA) is now widely appreciated. The disease is mediated by activated pro-inflammatory, self-reactive T helper cells, instigating the chronic autoimmune response characteristic of rheumatoid inflammation. Natural killer T (NKT) cells are a distinctive population of T cells thought to protect self-tissues from damaging inflammatory immune responses, and are often recognized as a regulatory T cell subtype, regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…Several studies have provided evidence for a pathogenic role of NKT cells in CIA (reviewed in [122]). One group of investigators showed that blockade of the interaction between CD1d and NKT cells with anti-CD1d antibodies resulted in reduced arthritis [123].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Several studies have provided evidence for a pathogenic role of NKT cells in CIA (reviewed in [122]). One group of investigators showed that blockade of the interaction between CD1d and NKT cells with anti-CD1d antibodies resulted in reduced arthritis [123].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…The most commonly used animal model for RA, is induced by immunization of susceptible mouse strains with heterologous type-II collagen (CIA). Several studies suggest that NKT cells play a pathogenic role in CIA [75]. Studies performed with different mouse models for RA, have demonstrated that NKT play two opposite roles in arthritis, probably due to functional differences between type I NKT and type II NKT cells.…”
Section: Other Autoimmune Diseasesmentioning
confidence: 99%
“…Studies performed with different mouse models for RA, have demonstrated that NKT play two opposite roles in arthritis, probably due to functional differences between type I NKT and type II NKT cells. In fact type II NKT suppress arthritis while type I NKT cells play a pathogenic role in this disease [75][76][77][78]. Systemic lupus erythematosus (SLE) is mediated by autoantibodies directed against nuclear antigens a process controlled by autoreactive T helper cells and regulatory T cells.…”
Section: Other Autoimmune Diseasesmentioning
confidence: 99%
“…A series of studies have indicated that iNKT cells play an aggravating role in mouse models of inflammatory arthritis (reviewed in [118]). iNKT cell numbers were increased in liver and peripheral blood after induction of CIA and in the K/BxN arthritis model [119].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%